Erica Jong's Fear of Flying : A Feminist Study - Jassam, Hadeel Hatif (Al-Adab Journal, 2015)
Erica Jong’s Fear of Flying was written in 1973 , the year that witnessed the start of the first phase of the modern feminist movement which was characterized by consciousness-raising , rebellion and agitation. The aim of this paper is to investigate the attitude of American men and American society towards women, how they are treated and apprehended. It also explains how difficult it is for the society, to perpetuate the traditional roles assigned to women and men ,which uphold patriarchy as an ideology. The novel, as an example of feminist literature ,reflects women's attitude towards such societal traditions through its heroine , Isadora Wing ,who is seen as an embodiment of the new female consciousness .